Immunotherapy employing dendritic cell vaccination for patients with advanced or relapsed esophageal cancer. Issue 5 (27th July 2020) - Ogasawara, Masahiro; Miyashita, Mamiko; Yamagishi, Yuka; Ota, Shuichi
Abstract: The prognosis of patients with advanced esophageal cancer is poor despite the recent introduction of immune checkpoint inhibitors. In the present pilot study, we have evaluated the safety and the feasibility of Wilms' tumor 1 (WT1) peptide‐pulsed dendritic cell (DC) vaccination in combination with OK‐432 in patients with advanced or relapsed esophageal cancer. Fifteen eligible patients were enrolled. No severe adverse events related to the vaccinations were observed. Objective response rate and disease control rate were 20% and 40%, respectively. Median progression free survival and overall survival was 4.1 months and 7.0 months, respectively. WT1 peptide‐pulsed DC vaccinations augmented WT1specific immunity, which might be related to clinical outcome. These results indicate that DC‐based immunotherapy combined with a conventional chemotherapy is safe and feasible for patients in advanced stage of esophageal cancer.